2008
DOI: 10.1152/ajpheart.00982.2007
|View full text |Cite
|
Sign up to set email alerts
|

Wnt5a is expressed in murine and human atherosclerotic lesions

Abstract: Atherosclerosis is an inflammatory disease involving the accumulation of macrophages in the intima. Wnt5a is a noncanonical member of the Wnt family of secreted glycoproteins. Recently, human macrophages have been shown to express Wnt5a upon stimulation with bacterial pathogens in vitro and in granulomatous lesions in the lung of Mycobacterium tuberculosis-infected patients. Wnt5a expression has also been liked to Toll-like receptor-4 (TLR-4), an innate immune receptor implicated in atherosclerosis. These obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
140
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 124 publications
(146 citation statements)
references
References 31 publications
5
140
1
Order By: Relevance
“…A recent study has demonstrated a link between Wnt5a, toll‐like receptor 4, and pathological inflammation in human macrophages 124. Furthermore, the expression of Wnt5a has been demonstrated in murine and human atherosclerotic tissue 19. In addition to finding strong Wnt5a expression in macrophage‐rich regions of atherosclerotic lesions of apolipoprotein E–deficient mice on atherogenic diets, Wnt5a was also expressed in other regions of developed human plaques, such as in smooth muscle cells 19…”
Section: Implication Of Noncanonical Wnt Signaling In Vcmentioning
confidence: 99%
See 3 more Smart Citations
“…A recent study has demonstrated a link between Wnt5a, toll‐like receptor 4, and pathological inflammation in human macrophages 124. Furthermore, the expression of Wnt5a has been demonstrated in murine and human atherosclerotic tissue 19. In addition to finding strong Wnt5a expression in macrophage‐rich regions of atherosclerotic lesions of apolipoprotein E–deficient mice on atherogenic diets, Wnt5a was also expressed in other regions of developed human plaques, such as in smooth muscle cells 19…”
Section: Implication Of Noncanonical Wnt Signaling In Vcmentioning
confidence: 99%
“…They have a low proliferation rate that is maintained in check by the endothelium‐derived NO 12. Vascular injury triggers the phenotypic change to an active synthetic phenotype with an increased proliferation rate and secretory ability 19. Wnt signaling promotes VSMC survival,20 whereas silencing Wnt signaling reduces cell proliferation 21.…”
Section: Components Of the Vasculature Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…The 19 mammalian homologues have distinct expression patterns in embryonic and adult tissues and their during infections with mycobacteria, Gram-negative and Grampositive bacteria [2][3][4][5][6], and chronic inflammation in rheumatoid arthritis, atherosclerosis, obesity, and psoriasis [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%